Pedunculate Molgula species (Ascidiidae, Molgulidae) from the French Antarctic sector. Redescription and taxonomic revision - Monniot, Françoise; Dettai, Agnès (Zootaxa, 2015)
Following the Challenger Expedition in the southern Hemisphere, several international surveys have studied Antarctic ascidians. Several pedunculate Molgula were successively described under various names. From the French part of the Antarctic continent and the Kerguelen area, numerous Molgula were recently collected. They are described here in different species, but closely allied. Their taxonomy is revised with an historical review of the most detailed publications and a link to the ancient names.